No Return: The Gerry Irwin Story. UFO Abduction or Covert Operation? by David Booher - Bullard, Eddie (Journal of Scientific Exploration, 2018)
When I was 12 or 13 years old I read a UFO story that set off a four-bell alarm in my head: A young soldier named Gerry Irwin had a long drive ahead of him before he reached Fort Bliss, near El Paso, Texas. He was returning from leave after visiting family in Idaho and was now about halfway back to base, wending through a remote area of Utah on a cold February evening in 1959. A flash suddenly lit up the sky and the light glided down behind a nearby ridge. His first thought was it might be an airplane in trouble. Right or wrong, the responsible thing to do was to find out for sure, especially in a time before cell phones and a place with no buildings or traffic in sight. He wrote “Stop” in shoe polish on the side of his car and left a note for any passer-by that he had gone to investigate a possible crash, please notify law enforcement. In his overcoat he climbed the ridge to see where the light had landed. Later a search party found Irwin unconscious in the snow about a quarter-mile away. For nearly 24 hours he remained unconscious in the Cedar City hospital; no efforts by the doctors could waken him. During this time he muttered something about a jacket on a bush. When consciousness returned he learned that there was no plane crash, also that the jacket he had worn under his overcoat was not found. And he had no memory of anything that happened from the time he set off on foot from his car.